2020
DOI: 10.1016/j.nmd.2020.08.355
|View full text |Cite
|
Sign up to set email alerts
|

Mortality rates and causes of death in Swedish Myasthenia Gravis patients

Abstract: Myasthenia Gravis (MG) is an autoimmune disease with several comorbidities, however information on MG mortality remains sparse. We conducted a nationwide register-based study on mortality rates and causes of death among Swedish MG patients. Data was acquired from four Swedish National Board of Health and Welfare registers. A total of 4559 MG patients (2522 women, 55.3%) being alive entering the year 2006, were identified. 1121 patients (562 women, 50.1%) died during 2006-2016. Age-and gender-standardized morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…Mortality in our sample was similar to that reported in most recent studies [23]. Overall mortality was higher in thymomatous patients.…”
Section: Discussionsupporting
confidence: 90%
“…Mortality in our sample was similar to that reported in most recent studies [23]. Overall mortality was higher in thymomatous patients.…”
Section: Discussionsupporting
confidence: 90%
“…Among Swedish MG patients in a nationwide register-based cohort study, the most common cause of death was cancer, 1 which agreed with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…
The common causes of death in myasthenia gravis (MG) patients were raised as cancer, cardiovascular diseases, cerebrovascular diseases, and respiratory tract infections such as pneumonia. [1][2][3] Crisis in patients with MG is defined as the need to intubate patients to provide ventilatory support or airway protection. 4 Crisis is caused by myasthenic, cholinergic, or prolonged intubation after surgery.
…”
mentioning
confidence: 99%
“…The antibody response in MG is not different from that in healthy subjects, even in those with IST except RTX (70). Study evaluating the cause of death in Swedish MG patients reveals influenza/pneumonia is a striking contributor (88). A 10year longitudinal study found a significant 48% reduction in mortality and a 27% reduction in hospital admissions after influenza vaccination in AIID patients (89).…”
Section: Risk-benefit Assessment Of Vaccination In Mgmentioning
confidence: 98%